Long-term weight gain and economic impact in pigs castrated under local anaesthesia - Telles, F. G. [UNESP]; Luna, S. P.L. [UNESP]; Teixeira, G. [UNESP]; Berto, D. A. [UNESP] (Elsevier, 2016)
Castration is a controversial practice in swine production because in some countries is still performed without anaesthesia, and therefore causes intense suffering and stress to animals. This study investigated the effect of pre-surgical administration of local anaesthesia (LA) on the growth performance of piglets until the end of the growth phase (102 days). Piglets aged 3 to 5 days were selected in pairs of similar weights and same age. They were originated from 22 litters. The groups were randomly assigned to one of two treatments. Castration was performed with (LA; n = 45) or without (NLA; n = 45) intra-testicular administration of 0.5 mL of 2% lidocaine plus adrenaline per testicle, administered by an automatic repeating vaccinator. Castration was performed 10 min later. Average daily weight gain and economic impact were evaluated between the intervals before castration until 21 (weaning phase), before castration until 60 (end of the initial nursery phase) and before castration until 102 (growth phase) days of age. Average daily weight gain data were analyzed by comparing the average daily weight gain between the weaning phase, 60 and 102 days of age versus the initial weight (pre-castration). At the end of the growing phase, animals treated with LA showed greater weight gain than animals castrated without anaesthesia. LA also showed improved cost:benefit ratio and theore might provide greater economic benefit under the conditions used in this study. Our findings have proved that castration with LA improves long-term weight gain of piglets.
Keywords: Castration; Economic Indexes; Lidocaine; Swine; Weight Gain